Strategi Pemberdayaan UMKM oleh Lembaga Amil Zakat Nurul Falah di Ketintang Surabaya - Novia Ayu Lestari; Agus Afandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the community empowerment strategy implemented by Lazis Nurul Falah in supporting Micro, Small, and Medium Enterprises (MSMEs) in Ketintang, Surabaya. The research used a qualitative descriptive approach with observation, interview, and documentation techniques. Data were collected directly during the distribution of business capital assistance and mentoring of beneficiaries. The results show that the empowerment program focused on improving economic independence through financial aid, business equipment, and moral support from volunteers. Although conducted modestly, the program had a significant impact on beneficiaries’ confidence and motivation to continue their businesses. It also strengthened social and Islamic values such as ta‘āwun (mutual help) and built harmonious relations between the institution, volunteers, and the community. The study concludes that empowerment based on collaboration and social proximity can create positive change and serve as an effective model to promote community economic independence.